2012
DOI: 10.1001/jama.2012.5034
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aspirin Use With Major Bleeding in Patients With and Without Diabetes

Abstract: ContextThe benefit of aspirin for the primary prevention of cardiovascular events is relatively small for individuals with and without diabetes. This benefit could easily be offset by the risk of hemorrhage.Objective To determine the incidence of major gastrointestinal and intracranial bleeding episodes in individuals with and without diabetes taking aspirin. Design, Setting, and ParticipantsA population-based cohort study, using administrative data from 4.1 million citizens in 12 local health authorities in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 37 publications
10
141
2
2
Order By: Relevance
“…37 A population-based study of aspirin-related bleeding showed that aspirin did not increase gastrointestinal bleeding even in patients with diabetes mellitus, although patients with diabetes mellitus had a higher rate of bleeding than those without diabetes mellitus. 38 In the JPAD2 study, long-term follow-up revealed that low-dose aspirin certainly increased the rate of gastrointestinal bleeding in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…37 A population-based study of aspirin-related bleeding showed that aspirin did not increase gastrointestinal bleeding even in patients with diabetes mellitus, although patients with diabetes mellitus had a higher rate of bleeding than those without diabetes mellitus. 38 In the JPAD2 study, long-term follow-up revealed that low-dose aspirin certainly increased the rate of gastrointestinal bleeding in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…El riesgo de hemorragia probablemente sea la RAM más frecuente y mejor documentada a través de los casos recogidos en la bibliografía (21)(22)(23)(24). En este estudio 5 pacientes refirieron tener antecedentes de úlcera y la utilización de medicamentos cuyo uso conjunto incrementa el riesgo de hemorragias, bien por daño directo o bien por afectar a la coagulación, como es el caso de los corticoides (5 casos), los inhibidores selectivos de la recaptación de serotonina (ISRS) (2 casos), los anticoagulantes (3 casos) o los trombolíticos (1 caso), además de los 19 que utilizaban otro AINE.…”
Section: Originalesunclassified
“…1,2 However, it also increases the risk of gastrointestinal bleeding, even at low doses. 1,3,4 The effect on stroke is mixed: Aspirin may slightly reduce the risk of ischemic strokes, but it also increases the less frequent hemorrhagic type. 1 Several systematic reviews, meta-analyses, and evidence-based clinical guidelines have quantified these effects and offered opinions about the utility of aspirin for primary prevention based on counts of the beneficial and detrimental events.…”
Section: Introductionmentioning
confidence: 99%